A method for preparing amorphous CON material using gas packaging
Through gas packaging and high-temperature and high-pressure treatment, the problem of poor stability of CON materials in the prior art under normal pressure conditions was solved, and amorphous CON materials with normal pressure were successfully prepared, which enhanced its practical application potential.
Patent Information
- Application Number
- CN202510175387.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-18
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2045-02-18
AI Technical Summary
The prior art is difficult to stabilize the preparation of high energy density CON materials under normal pressure conditions, and their stability is poor, which limits its practical application.
Using the gas packaging method, the CO-N2 mixture was encapsulated at high pressure, and in-situ heat treatment was performed under high temperature and high pressure conditions to prepare amorphous CON material with normal pressure stability.
The preparation of amorphous CON materials that exist stably under normal pressure conditions is realized, the stability of the material is improved, and strong guidance is provided for its practical application.
Smart Images

Figure CN119661294B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of amorphous CON material preparation, and specifically discloses a method for preparing an amorphous CON material by gas packaging. Background Art
[0002] High energy density materials not only have important applications in industrial metallurgy, military explosives, and aerospace propellants, but also play a huge role in modern agricultural construction. For example, in land reclamation, high energy density materials can be used for blasting operations to remove rocks, trees or other obstacles. Theoretical calculations show that the energy density of polymerized nitrogen materials is more than three times that of HMX (high explosives), making it a new type of high energy density material with great potential.
[0003] However, the synthesis conditions of pure nitrogen polymer nitrogen materials are extremely harsh. They need to be synthesized under pressure conditions greater than 110 GPa, and decompose when the pressure is released to 40 GPa. They have poor stability and cannot be stable at normal pressure, which limits their practical applications. Since molecular nitrogen and carbon monoxide both have high-energy triple bonds under ambient conditions, theory predicts that CON materials can significantly improve the stability of materials while retaining high energy density characteristics as much as possible. Therefore, it is of great significance to find an effective synthesis route to prepare CON materials.
[0004] In the existing research on the preparation of CON materials, the Italian research team conducted high-pressure light irradiation experiments on CO-N2 mixed precursor materials with volume ratios of 1:9 and 0.5:9.5. After irradiating the samples with a 514 nm laser of 100-500mw for several hours in the pressure range of 6-26 GPa, amorphous CON materials containing CN and C=O were prepared. However, the CON materials prepared by this method had a low degree of polymerization, and the samples decomposed into gas when the pressure was reduced to 1-2 GPa, and a stable solid sample at normal pressure could not be obtained. The US research team conducted high-temperature and high-pressure studies on CO-N2 mixed precursor materials with various volume ratios, and prepared the crystalline P43-CON2 material under 45 GPa pressure conditions. The structure was consistent with the previous theoretical prediction, and its characteristics were an octagonal ring structure composed of CN, CO and NN single bonds, but when the pressure was reduced to 20 GPa, the crystalline structure was not stable. When the material is heated, it decomposes and transforms into ε-phase N2, which cannot be intercepted to ambient pressure conditions. There is no report on CON materials that are stable at normal pressure. Based on the analysis of existing data, the selection of appropriate precursors and differences in temperature and pressure conditions are important factors affecting the synthesis and stability of CON materials. Therefore, in view of this, a method for preparing amorphous CON materials using gas encapsulation is provided to provide strong guidance for the actual production application of CON materials. Summary of the invention
[0005] The object of the present invention is to provide a method for preparing an amorphous CON material using gas packaging, so as to provide powerful guidance for the actual production and application of the CON material.
[0006] In order to achieve the above object, the basic scheme of the present invention provides a method for preparing an amorphous CON material using gas packaging, including sample packaging and product synthesis, wherein the sample packaging includes the following steps:
[0007] Step S1, machining a circular sample cavity with a diameter of 150 um on a rhenium sheet with a thickness of 25 um;
[0008] Step S2, placing the processed rhenium sheet in anhydrous ethanol for ultrasonic cleaning;
[0009] Step S3, placing the rhenium sheet in a high-pressure gas sealed chamber;
[0010] Step S4, pre-compressing CO-N2 with a volume ratio of 7:3 to a mixed gas of 120-130 MPa;
[0011] Step S5, passing the high-pressure mixed gas into the sample cavity for packaging, and the pressure in the sample cavity after the sample is packaged is 0.5-1.0 GPa;
[0012] The product synthesis includes the following steps:
[0013] Step Q1, after completing the sample packaging, uniformly pressurize the sample chamber to 55 - 89 GPa;
[0014] Step Q2, subjecting the sample to in-situ heat treatment for 2-3 min at a temperature of 1800-2000K;
[0015] Step Q3, after heating, the sample is quickly quenched to room temperature, the pressure in the sample chamber is slowly reduced to ambient conditions, the rhenium sheet is taken out, and a brown-yellow transparent amorphous CON material stored in the rhenium sheet sample chamber is obtained.
[0016] Further, in the step S1, a 5*5*0.25 cm rhenium sheet is pre-pressed to a thickness of 25 um using a diamond anvil;
[0017] In step S2, the cleaned rhenium sheet is returned to the diamond anvil;
[0018] In the step S3, the diamond anvil is transferred to a high-pressure gas sealed chamber;
[0019] In step S4, the diamond anvil is taken out from the gas-tight chamber.
[0020] Furthermore, in the step S3, a ruby with a diameter of 10-15 um is placed at the edge of the sample cavity, and in the step Q1, the pressure in the sample cavity is calibrated by the fluorescence peak shift of the micro ruby.
[0021] Furthermore, in step Q2, a laser is used to perform in-situ heat treatment on the sample, and the laser wavelength is 1064 nm.
[0022] Furthermore, in step Q2, the position of the diamond anvil is changed by a three-dimensional precision translation stage so as to achieve complete heating preparation of the entire sample.
[0023] Furthermore, the pressurizing condition of step Q1 is 55 GPa, and the heating temperature of step Q2 is 1800K.
[0024] Furthermore, the pressurization condition of step Q1 is 89 GPa, and the heating temperature of step Q2 is 2000K.
[0025] Based on the same inventive concept, the present invention provides an amorphous CON material encapsulated by gas, wherein the amorphous CON material is made by the above-mentioned preparation method.
[0026] Compared with the prior art, the present invention has at least the following technical effects:
[0027] 1. The DAC loading and sealing of the CO-N2 mixed gas was achieved through the gas packaging system. Compared with the traditional low-temperature sample packaging, this method is safer and faster in a completely closed gas path. It also avoids the disadvantage of introducing H2O in the air into the sample cavity in an open low-temperature sample packaging system, which is conducive to the preparation of higher purity CON samples.
[0028] 2. Use a high-power yttrium aluminum garnet (YAG 1064nm) laser to focus on the sample cavity through the constructed microscopic optical path to heat the sample. Laser heating can provide a higher reaction temperature while achieving rapid temperature rise and fall of the sample cavity. Rapid heating and quenching of the sample can further promote the formation of amorphous stable structure.
[0029] 3. The amorphous CON material synthesized according to the amorphous CON preparation method has good stability and can exist stably in a normal pressure environment. The high-temperature and high-pressure preparation method of an amorphous CON high-energy density material of the present invention provides powerful guidance for the actual production and application of CON materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For those skilled in the art, other drawings can be obtained based on these drawings without creative work.
[0031] Figure 1 A flow chart showing a method for preparing an amorphous CON material using gas encapsulation is shown;
[0032] Figure 2 The 514nm Raman characteristic spectrum in the 0.5 GPa sample cavity after CO-N2 gas packaging is shown;
[0033] Figure 3 The in-situ infrared absorption characteristic spectrum of CO-N255 GPa +1800K sample is shown;
[0034] Figure 4 The in-situ infrared absorption characteristic spectrum of CO-N289 GPa +2000K sample is shown;
[0035] Figure 5 The 514 nm Raman characteristic spectrum comparison of CO-N2 precursor material and prepared amorphous CON material is shown;
[0036] Figure 6 The SEM elemental analysis of CON material prepared at 55 GPa + 1800K is shown;
[0037] Figure 7 The SEM elemental analysis of CON material prepared at 89 GPa + 2000K is shown;
[0038] Figure 8 The high-resolution and selected-area electron diffraction patterns of the CON material prepared at 55 GPa + 1800K are shown;
[0039] Fig. 9 The atmospheric pressure TEM high-resolution and selected area electron diffraction patterns of CON material prepared at 89 GPa + 2000K are shown. DETAILED DESCRIPTION
[0040] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation mode, structure, characteristics and effects of the present invention are described in detail below in combination with the accompanying drawings and preferred embodiments.
[0041] A method for preparing an amorphous CON material using gas packaging, Experimental Example 1 includes a sample packaging process and a product synthesis process.
[0042] The specific steps of sample packaging are as follows:
[0043] Step S1, using a diamond anvil to pre-press a 5*5*0.25 cm rhenium sheet to a thickness of about 25 um, and using a laser micromachining system to machine a 150 um diameter circular sample cavity at the center of the indentation.
[0044] Step S2, ultrasonically clean the processed material in anhydrous ethanol for 10 min to remove metal debris, and after cleaning, return it to the diamond anvil according to the position during pre-compression.
[0045] Step S3, after placing a ruby with a diameter of 10-15 um at the edge of the sample chamber, close the diamond anvil and reset the pressure screw to the equilibrium position. The reset diamond anvil is transferred to the high-pressure gas sealing chamber, and four pressure screws and the gear box are connected through a 12mm long hexagon-hexagon adapter column. The other end of the high-pressure gas sealing chamber is sealed by a four-leaf metal piston, and the safety screw is screwed in after rotating it to the locked position to prevent the high-pressure gas from rushing out.
[0046] Step S4, pre-compressing CO-N2 to 120-130 MPa by a gas two-stage piston type pressure pump to obtain a sufficiently high density reaction precursor. During this process, the volume ratio of CO to N2 is 7:3.
[0047] Step S5, as the gear box is controlled by the torsion motor to rotate counterclockwise, the pressure screw is driven to rotate to open the sample chamber of the diamond anvil, and after waiting for 10-30 seconds to allow the 120-130 MPa high-pressure mixed gas to completely enter the sample chamber, the gear box is controlled by the torsion motor to rotate clockwise to drive the pressure screw to close the diamond anvil to form a completely closed sample chamber, and the remaining gas is discharged to the outdoor ventilation duct through the pressure relief pipe after treatment. After it is completely emptied, the diamond anvil is taken out from the gas sealing chamber to complete the packaging of the gas precursor sample in the sample chamber. The pressure in the sample chamber after the sample is packaged is 0.5-1.0 GPa.
[0048] The 514 nm Raman characteristic spectrum of the sample under 0.5 GPa pressure is shown in the figure below. Figure 2 As shown, at this time, only characteristic Raman signals of CO and N2 exist in the spectrum, and the intensity ratio is consistent with the initial volume ratio of the CO-N2 reaction precursor, indicating that impurity-free and uniform encapsulation of CO-N2 is achieved through the gas encapsulation system.
[0049] The steps for product synthesis are as follows:
[0050] Step Q1, after completing the sample packaging, the sample cavity is uniformly pressurized to 55 GPa using an Allen wrench, and the pressure in the sample cavity is calibrated by the micro-ruby fluorescence peak shift.
[0051] Step Q2, using a high-power yttrium aluminum garnet (YAG) laser as a laser source with a wavelength of 1064 nm, focusing the 1064 nm laser on the sample surface through a microscopic imaging optical path and a 20x telephoto high-transmittance lens to perform in-situ heat treatment on the sample. In this embodiment, the in-situ heat treatment uses high-temperature in-situ heating treatment, and the heating temperature is 1800 K. During the heating process, the sample reacts violently and presents bright white light. The heating process lasts for 2-3 minutes. The position of the diamond anvil is changed by a three-dimensional precision translation stage to achieve complete heating preparation of the entire sample.
[0052] Step Q3, after laser heating, the sample is quickly quenched to room temperature, and the pressure load on the diamond anvil is removed by rotating the pressure screw counterclockwise with an Allen wrench, so that the pressure in the sample chamber is slowly reduced to ambient conditions, and the diamond anvil device is opened to take out the rhenium sheet to obtain the brown-yellow transparent amorphous CON material stored in the rhenium sheet sample chamber.
[0053] In-situ characteristic infrared spectra of CON materials prepared at 55 GPa high temperature and high pressure Figure 3 As shown by Figure 3 It can be seen that after the laser subjected the sample to high-pressure heating treatment, CON polymer materials connected by CN, CO, NN and C=O single and double bonds were formed.
[0054] The packaging process of Experimental Example 2 is the same as that of Experimental Example 1. The difference between Experimental Example 2 and Experimental Example 1 is that in step Q1, after the sample is packaged, the sample cavity is uniformly pressurized to 89 GPa by an Allen wrench. In step Q2, the temperature is heated to 2000K. The in-situ characteristic infrared spectrum of the CON material prepared at 89 GPa high temperature and high pressure is as follows: Figure 4 As shown by Figure 4 It can be seen that after the sample was treated with high pressure laser heating, a CON polymer material with CN, CO and NN single bonds was formed.
[0055] Comparative Example 1 includes a sample packaging process and a product synthesis process.
[0056] The specific steps of sample packaging are as follows:
[0057] Step S1, using a diamond anvil to pre-press a 5*5*0.25 cm rhenium sheet to a thickness of about 25 um, and using a laser micromachining system to machine a 150 um diameter circular sample cavity at the center of the indentation.
[0058] Step S2, ultrasonically clean the processed material in anhydrous ethanol for 10 min to remove metal debris, and after cleaning, return it to the diamond anvil according to the position during pre-compression.
[0059] Step S3, after placing a ruby with a diameter of 10-15 um at the edge of the sample chamber, close the diamond anvil and reset the pressure screw to the equilibrium position. The reset diamond anvil is transferred to the high-pressure gas sealing chamber, and four pressure screws and the gear box are connected through a 12mm long hexagon-hexagon adapter column. The other end of the high-pressure gas sealing chamber is sealed by a four-leaf metal piston, and the safety screw is screwed in after rotating it to the locked position to prevent the high-pressure gas from rushing out.
[0060] Step S4, pre-compressing CO-N2 to 120-130 MPa by a gas two-stage piston type pressure pump to obtain a sufficiently high density reaction precursor. During this process, the volume ratio of CO to N2 is 7:3.
[0061] Step S5, as the gear box is controlled by the torsion motor to rotate counterclockwise, the pressure screw is driven to rotate to open the sample chamber of the diamond anvil, and after waiting for 10-30 seconds to allow the 120-130 MPa high-pressure mixed gas to completely enter the sample chamber, the gear box is controlled by the torsion motor to rotate clockwise to drive the pressure screw to close the diamond anvil to form a completely closed sample chamber, and the remaining gas is discharged to the outdoor ventilation duct through the pressure relief pipe after treatment. After it is completely emptied, the diamond anvil is taken out from the gas sealing chamber to complete the packaging of the gas precursor sample in the sample chamber. After the sample is packaged, the pressure in the sample chamber is 0.5-1.0GPa.
[0062] The steps for product synthesis are as follows:
[0063] Step Q1, after completing the sample packaging, the sample cavity is uniformly pressurized to 25 GPa using an Allen wrench, and the pressure in the sample cavity is calibrated by the micro-ruby fluorescence peak shift.
[0064] Step Q2, using a high-power yttrium aluminum garnet (YAG) laser as a laser source with a wavelength of 1064 nm, focusing the 1064 nm laser on the sample surface through a microscopic imaging optical path and a 20x telephoto high-transmittance lens to perform in-situ heat treatment on the sample. In this embodiment, the in-situ heat treatment uses high-temperature in-situ heating treatment, and the heating temperature is 1800 K. During the heating process, the sample reacts violently and presents bright white light. The heating process lasts for 2-3 minutes. The position of the diamond anvil is changed by a three-dimensional precision translation stage to achieve complete heating preparation of the entire sample.
[0065] Step Q3, after laser heating, the sample is quickly quenched to room temperature, and the pressure load on the diamond anvil is removed by rotating the pressure screw counterclockwise with an Allen wrench, so that the pressure in the sample chamber is slowly reduced to ambient conditions, the diamond anvil device is opened, and the rhenium sheet is taken out. The solid sample in the sample chamber is a black opaque amorphous carbon material.
[0066] Comparative Example 2 includes a sample packaging process and a product synthesis process.
[0067] The specific steps of sample packaging are as follows:
[0068] Step S1, using a diamond anvil to pre-press a 5*5*0.25 cm rhenium sheet to a thickness of about 25 um, and using a laser micromachining system to machine a 150 um diameter circular sample cavity at the center of the indentation.
[0069] Step S2, ultrasonically clean the processed material in anhydrous ethanol for 10 min to remove metal debris, and after cleaning, return it to the diamond anvil according to the position during pre-compression.
[0070] Step S3, after placing a ruby with a diameter of 10-15 um at the edge of the sample chamber, close the diamond anvil and reset the pressure screw to the equilibrium position. The reset diamond anvil is transferred to the high-pressure gas sealing chamber, and four pressure screws and the gear box are connected through a 12mm long hexagon-hexagon adapter column. The other end of the high-pressure gas sealing chamber is sealed by a four-leaf metal piston, and the safety screw is screwed in after rotating it to the locked position to prevent the high-pressure gas from rushing out.
[0071] Step S4, pre-compressing CO-N2 to 120-130 MPa by a gas two-stage piston type pressure pump to obtain a sufficiently high-density reaction precursor. During this process, the volume ratio of CO to N2 is 3:7.
[0072] Step S5, as the gear box is controlled by the torsion motor to rotate counterclockwise, the pressure screw is driven to rotate to open the sample chamber of the diamond anvil, and after waiting for 10-30 seconds to allow the 120-130 MPa high-pressure mixed gas to completely enter the sample chamber, the gear box is controlled by the torsion motor to rotate clockwise to drive the pressure screw to close the diamond anvil to form a completely closed sample chamber, and the remaining gas is discharged to the outdoor ventilation duct through the pressure relief pipe after treatment. After it is completely emptied, the diamond anvil is taken out from the gas sealing chamber to complete the packaging of the gas precursor sample in the sample chamber. After the sample is packaged, the pressure in the sample chamber is 0.5-1.0GPa.
[0073] The steps for product synthesis are as follows:
[0074] Step Q1, after completing the sample packaging, the sample cavity is uniformly pressurized to 55 GPa using an Allen wrench, and the pressure in the sample cavity is calibrated by the micro-ruby fluorescence peak shift.
[0075] Step Q2, using a high-power yttrium aluminum garnet (YAG) laser as a laser source with a wavelength of 1064 nm, focusing the 1064 nm laser on the sample surface through a microscopic imaging optical path and a 20x telephoto high-transmittance lens to perform in-situ heat treatment on the sample. In this embodiment, the in-situ heat treatment uses high-temperature in-situ heating treatment, and the heating temperature is 1800 K. During the heating process, the sample reacts violently and presents bright white light. The heating process lasts for 2-3 minutes. The position of the diamond anvil is changed by a three-dimensional precision translation stage to achieve complete heating preparation of the entire sample.
[0076] In step Q3, after laser heating, the sample is quickly quenched to room temperature, and the pressure load on the diamond anvil is removed by rotating the pressure screw counterclockwise with an Allen wrench, so that the pressure in the sample chamber is slowly reduced to ambient conditions. The diamond anvil device is opened to take out the rhenium sheet, and no solid sample is obtained after the gas in the sample chamber escapes.
[0077] Comparative Example 3 includes a sample packaging process and a product synthesis process.
[0078] The specific steps of sample packaging are as follows:
[0079] Step S1, using a diamond anvil to pre-press a 5*5*0.25 cm rhenium sheet to a thickness of about 25 um, and using a laser micromachining system to machine a 150 um diameter circular sample cavity at the center of the indentation.
[0080] Step S2, ultrasonically clean the processed material in anhydrous ethanol for 10 min to remove metal debris, and after cleaning, return it to the diamond anvil according to the position during pre-compression.
[0081] Step S3, after placing a ruby with a diameter of 10-15 um at the edge of the sample chamber, close the diamond anvil and reset the pressure screw to the equilibrium position. The reset diamond anvil is transferred to the high-pressure gas sealing chamber, and four pressure screws and the gear box are connected through a 12mm long hexagon-hexagon adapter column. The other end of the high-pressure gas sealing chamber is sealed by a four-leaf metal piston, and the safety screw is screwed in after rotating it to the locked position to prevent the high-pressure gas from rushing out.
[0082] Step S4, pre-compressing CO-N2 to 120-130 MPa by a gas two-stage piston type pressure pump to obtain a sufficiently high-density reaction precursor. During this process, the volume ratio of CO to N2 is 3:7.
[0083] Step S5, as the gear box is controlled by the torsion motor to rotate counterclockwise, the pressure screw is driven to rotate to open the sample chamber of the diamond anvil, and after waiting for 10-30 seconds to allow the 120-130 MPa high-pressure mixed gas to completely enter the sample chamber, the gear box is controlled by the torsion motor to rotate clockwise to drive the pressure screw to close the diamond anvil to form a completely closed sample chamber, and the remaining gas is discharged to the outdoor ventilation duct through the pressure relief pipe after treatment. After it is completely emptied, the diamond anvil is taken out from the gas sealing chamber to complete the packaging of the gas precursor sample in the sample chamber. After the sample is packaged, the pressure in the sample chamber is 0.5-1.0GPa.
[0084] The steps for product synthesis are as follows:
[0085] Step Q1, after completing the sample packaging, the sample cavity is uniformly pressurized to 89 GPa using an Allen wrench, and the pressure in the sample cavity is calibrated by the micro-ruby fluorescence peak shift.
[0086] Step Q2, using a high-power yttrium aluminum garnet (YAG) laser as a laser source with a wavelength of 1064 nm, focusing the 1064 nm laser on the sample surface through a microscopic imaging optical path and a 20x telephoto high-transmittance lens to perform in-situ heat treatment on the sample. In this embodiment, the in-situ heat treatment uses high-temperature in-situ heating treatment, and the heating temperature is 2000 K. During the heating process, the sample reacts violently and presents bright white light. The heating process lasts for 2-3 minutes. The position of the diamond anvil is changed by a three-dimensional precision translation stage to achieve complete heating preparation of the entire sample.
[0087] In step Q3, after laser heating, the sample is quickly quenched to room temperature, and the pressure load on the diamond anvil is removed by rotating the pressure screw counterclockwise with an Allen wrench, so that the pressure in the sample chamber is slowly reduced to ambient conditions. The diamond anvil device is opened to take out the rhenium sheet, and no solid sample is obtained after the gas in the sample chamber escapes.
[0088] Comparative Example 4 includes a sample packaging process and a product synthesis process.
[0089] The specific steps of sample packaging are as follows:
[0090] Step S1, using a diamond anvil to pre-press a 5*5*0.25 cm rhenium sheet to a thickness of about 25 um, and using a laser micromachining system to machine a 150 um diameter circular sample cavity at the center of the indentation.
[0091] Step S2, ultrasonically clean the processed material in anhydrous ethanol for 10 min to remove metal debris, and after cleaning, return it to the diamond anvil according to the position during pre-compression.
[0092] Step S3, after placing a ruby with a diameter of 10-15 um at the edge of the sample chamber, close the diamond anvil and reset the pressure screw to the equilibrium position. The reset diamond anvil is transferred to the high-pressure gas sealing chamber, and four pressure screws and the gear box are connected through a 12mm long hexagon-hexagon adapter column. The other end of the high-pressure gas sealing chamber is sealed by a four-leaf metal piston, and the safety screw is screwed in after rotating it to the locked position to prevent the high-pressure gas from rushing out.
[0093] Step S4, pre-compressing CO-N2 to 120-130 MPa by a gas two-stage piston type pressure pump to obtain a sufficiently high density reaction precursor. During this process, the volume ratio of CO to N2 is 1:9.
[0094] Step S5, as the gear box is controlled by the torsion motor to rotate counterclockwise, the pressure screw is driven to rotate to open the sample chamber of the diamond anvil, and after waiting for 10-30 seconds to allow the 120-130 MPa high-pressure mixed gas to completely enter the sample chamber, the gear box is controlled by the torsion motor to rotate clockwise to drive the pressure screw to close the diamond anvil to form a completely closed sample chamber, and the remaining gas is discharged to the outdoor ventilation duct through the pressure relief pipe after treatment. After it is completely emptied, the diamond anvil is taken out from the gas sealing chamber to complete the packaging of the gas precursor sample in the sample chamber. After the sample is packaged, the pressure in the sample chamber is 0.5-1.0GPa.
[0095] The steps for product synthesis are as follows:
[0096] Step Q1, after completing the sample packaging, the sample cavity is uniformly pressurized to 55 GPa using an Allen wrench, and the pressure in the sample cavity is calibrated by the micro-ruby fluorescence peak shift.
[0097] Step Q2, using a high-power yttrium aluminum garnet (YAG) laser as a laser source with a wavelength of 1064 nm, focusing the 1064 nm laser on the sample surface through a microscopic imaging optical path and a 20x telephoto high-transmittance lens to perform in-situ heat treatment on the sample. In this embodiment, the in-situ heat treatment uses high-temperature in-situ heating treatment, and the heating temperature is 1800 K. During the heating process, the sample reacts violently and presents bright white light. The heating process lasts for 2-3 minutes. The position of the diamond anvil is changed by a three-dimensional precision translation stage to achieve complete heating preparation of the entire sample.
[0098] In step Q3, after laser heating, the sample is quickly quenched to room temperature, and the pressure load on the diamond anvil is removed by rotating the pressure screw counterclockwise with an Allen wrench, so that the pressure in the sample chamber is slowly reduced to ambient conditions. The diamond anvil device is opened to take out the rhenium sheet, and no solid sample is obtained after the gas in the sample chamber escapes.
[0099] The characteristic Raman spectra of the brown-yellow transparent CON materials obtained in Example 1 and Example 2 were collected by 514 nm Raman spectroscopy as shown in FIG4 . The Raman spectra of the precursor CO-N2 were compared with those of the precursor, indicating that the precursor was transformed from a molecular phase into a stable amorphous CON material at normal pressure under high temperature and high pressure conditions. Due to the disordered amorphous structure, the characteristic peaks of the CON materials were in the range of 1480-1600 cm -1 In addition, scanning electron microscope (SEM) and transmission electron microscope (TEM) test samples of the samples obtained in Example 1 and Example 2 were prepared, and the results were as follows Figure 6 , Figure 7 as well as Figure 8 , Fig. 9 As shown in the figure, the N content of the CON material prepared at 55 GPa + 1800 K is 22.8%, and when the pressure is further increased to 89 GPa + 2000 K, the nitrogen content reaches 35.7%. The reason why the N content exceeds 30% is that the CO2 produced during the heating process can remove some O atoms. At the same time, no regular lattice fringes appear in the transmission electron microscopy of the samples prepared at 55 GPa + 1800 K and 89 GPa + 2000 K, and the selected area electron diffraction in the upper right inset also shows that the sample is an amorphous structure.
[0100] By comparing Experimental Example 1 with Comparative Example 1, Comparative Example 2, Comparative Example 4, and by comparing Experimental Example 2 with Comparative Example 3, and combining Figure 6 , Figure 7 as well as Figure 8 , Fig. 9 It can be seen that the high temperature and high pressure preparation method of an amorphous CON material of the present invention obtains an amorphous CON material that is stable at normal pressure.
[0101] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A method for preparing an amorphous CON material using gas encapsulation, characterized in that: Including sample packaging and product synthesis, the sample packaging includes the following steps: Step S1, machining a circular sample cavity with a diameter of 150 um on a rhenium sheet with a thickness of 25 um; Step S2, placing the processed rhenium sheet in anhydrous ethanol for ultrasonic cleaning; Step S3, placing the rhenium sheet in the gas sealing chamber; Step S4, pre-compressing CO-N2 with a volume ratio of 7:3 to a mixed gas of 120-130 MPa; Step S5, passing a mixed gas of 120-130 MPa into the sample cavity for packaging, and the pressure in the sample cavity after the sample is packaged is 0.5-1.0 GPa; The product synthesis includes the following steps: Step Q1, after completing the sample packaging, uniformly pressurize the sample chamber to 55 - 89 GPa; Step Q2, subjecting the sample to in-situ heat treatment for 2-3 min at a temperature of 1800-2000K; Step Q3, after heating, the sample is quickly quenched to room temperature, the pressure in the sample chamber is slowly reduced to ambient conditions, the rhenium sheet is taken out, and a brown-yellow transparent amorphous CON material stored in the rhenium sheet sample chamber is obtained.
2. The method for preparing amorphous CON material using gas encapsulation according to claim 1, characterized in that: In the step S1, a 5*5*0.25 cm rhenium sheet is pre-pressed to a thickness of 25 um using a diamond anvil; In step S2, the cleaned rhenium sheet is returned to the diamond anvil; In step S3, the diamond anvil is transferred to a gas-tight chamber; In step S4, the diamond anvil is taken out from the gas-tight chamber.
3. The method for preparing amorphous CON material using gas encapsulation according to claim 2, characterized in that: In the step S3, a ruby with a diameter of 10-15 um is placed at the edge of the sample cavity, and in the step Q1, the pressure in the sample cavity is calibrated by the fluorescence peak shift of the micro ruby.
4. The method for preparing amorphous CON material using gas encapsulation according to claim 3, characterized in that: In step Q2, laser is used to perform in-situ heat treatment on the sample, and the laser wavelength is 1064 nm.
5. The method for preparing amorphous CON material using gas encapsulation according to claim 4, characterized in that: In step Q2, the position of the diamond anvil is changed by a three-dimensional precision translation stage so as to achieve complete heating preparation of the entire sample.
6. A method for preparing amorphous CON material using gas encapsulation according to any one of claims 1 to 5, characterized in that: The pressurizing condition of step Q1 is 55 GPa, and the heating temperature of step Q2 is 1800K.
7. A method for preparing amorphous CON material using gas encapsulation according to any one of claims 1 to 5, characterized in that: The pressurizing condition of step Q1 is 89 GPa, and the heating temperature of step Q2 is 2000K.
8. An amorphous CON material encapsulated by gas, characterized in that: The amorphous CON material is made by the preparation method according to any one of claims 1 to 7.
Citation Information
Patent Citations
Polymeric CON energetic material and preparation method thereof
CN116850899A